2010
DOI: 10.1007/s12257-009-3091-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of fructose palmitate by lipase-catalyzed esterification in ionic liquids

Abstract: For the enhancement of enzyme activity, application of ultrasound irradiation on lipase-catalyzed esterification of fructose with palmitic acid in ionic liquids (ILs) mixture containing supersaturated fructose solution was investigated. In the mixture of [Bmim][TfO] and [Omim][Tf 2 N] (1:1, v/v), 1.44 times higher enzyme activity (29.2 µmoL/min/g) was achieved under ultrasound irradiation. Besides, ultrasound irradiation enhanced enzyme stability in viscous ILs mixture. After 5 times reuse of Novozym 435 and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 22 publications
(24 reference statements)
0
20
0
Order By: Relevance
“…3 The interest in biotechnological applications of ILs is growing not only for enzyme catalysis [4][5][6][7][8] but also for bioseparation process. [9][10] Their potential as media for biocatalytic reactions with remarkable yields 11 has been demonstrated, in addition to their enantioselectivity 12 and enzyme stability. 13 In bioseparations water miscible-ILs hold great potential as a feasible alternative for phase forming agents in aqueous biphasic systems (ABS) to replace conventional polymer and/or salt-rich phases, 14 for the purification of various enzymes including alcohol dehydrogenases, 15 lysozyme, 16 cyclodextrin glycosyltransferase, 17 peroxidases, 18 and lipases.…”
Section: Introductionmentioning
confidence: 99%
“…3 The interest in biotechnological applications of ILs is growing not only for enzyme catalysis [4][5][6][7][8] but also for bioseparation process. [9][10] Their potential as media for biocatalytic reactions with remarkable yields 11 has been demonstrated, in addition to their enantioselectivity 12 and enzyme stability. 13 In bioseparations water miscible-ILs hold great potential as a feasible alternative for phase forming agents in aqueous biphasic systems (ABS) to replace conventional polymer and/or salt-rich phases, 14 for the purification of various enzymes including alcohol dehydrogenases, 15 lysozyme, 16 cyclodextrin glycosyltransferase, 17 peroxidases, 18 and lipases.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ultrasound irradiation was applied in the enzymatic esterification of sugar with palmitic acid. As a result, in the mixture of 1-butyl-3-methylimidazolium trifluoromethanesulfonate ( 63 Lee et al 64 also observed enzyme activities in ILs were highly enhanced by using supersaturated solution under ultrasound irradiation in lipase-catalyzed esterifications of sugar with vinyl laurate or lauric acid. Furthermore, the stability of enzyme in ILs was not influenced by ultrasound irradiation.…”
Section: Synthesis Of Sucrose Esters In Organic Mediamentioning
confidence: 99%
“…59 4 ] as the solvent, yielded 50% of acetylated products. It was observed that the use of these N, N -dialkylimidazolium-based ILs as reaction media enhanced the selectivity of enzymes of Novozym 435 by Koo et al, 63,64 while the activity of enzymes in pure ILs was usually lower than those in conventional organic solvents. 29,62 Several studies have indicated that the use of external auxiliary physical fields or modification of enzymes can significantly increase the enzyme activity in ILs in the synthesis of sugar esters.…”
Section: Synthesis Of Sucrose Esters In Organic Mediamentioning
confidence: 99%
“…In this area, the most studied application of the IL/US combination is in the pretreatment of cellulose or lignocellulosic biomass to enhance enzymatic reactions. [144][145][146][147][148][149][150][151] For example, the cellulose saccharification ratio of bamboo powder pretreated in choline acetate was 1.7 times more efficient in the presence of low frequency ultrasound, and at room temperature (compared to 110 1C in silent conditions). 151 In the same way, ultrasonic pretreatment in imidazolium based ILs enhanced the enzymatic hydrolysis of kenaf powders.…”
Section: Lignocellulosic Biomass Valorizationmentioning
confidence: 99%
“…For example, we have seen that the combined technology produces exciting results for biomass pretreatment. [144][145][146][147][148][149][150][151] The combination with other innovative technologies represents a great potential in term of innovation, for example coupling with enzymatic catalysis for enhancing enzymatic activity in ILs. 51 In these cases, it will be important to study silent, coupled and non-coupled conditions separately, for comparison and to highlight the synergetic effects.…”
Section: Recommendations and Conclusionmentioning
confidence: 99%